POLA KONSUMSI IKAN LAUT DAN FAKTOR-FAKTOR YANG MEMENGARUHI KONSUMSI IKAN LAUT OLEH IBU HAMIL DI KECAMATAN KOTAAGUNG KABUPATEN TANGGAMUS - Bagus Lujeng Pangestu; Yaktiworo Indriani; Lina Marlina (Lampung University, 2020)
This study aims to analyze dietary patterns and factors that affect consumption of marine fish by pregnant women in Kotaagung Subdistrict of Tanggamus District. Respondents are 42 women at second and third trimester pregnancies who are recruited voluntarily. Data are analyzed descriptively using Multiattribute Fishbein and multiple linear regressions. The results showed that the consumption patterns of marine fish of pregnant women were illustrated by type of fish consumed, the amount of consumption, frequencies and locations of purchase. The types of fish consumed were cob, flying fish, anchovy, squid, bloated, and blue marlin. The dominant fish consumed by respondents was cob. The average amount of marine fish consumption by pregnant women was 42.12 grams/week and considered very low. The average consumption of protein was 6.02 grams (1.40 %AKE) per day and it was calculated that the maximum desireable dietary pattern (DDP) score for animal food was only 5.60 out of 24 of DDP ideal score. Purchase frequencies of marine fish were once to four times a week. Purchase locations were traditional markets and traveling traders. The factors that influenced the consumption of marine fish were prices of marine fish, pond fish, chicken, and tempeh, income, number of family members, and education.Key words: dietary pattern, marine fish, pregnant women.